Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Bahtera Adi Jaya Periode 2018-2022 - Satria, Rita; Imam, Didin Choerul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was conducted to find answers regarding the influence of motivation and work discipline on employee performance at PT Bahtera Adi Jaya during the period 2018-2022, both partially and simultaneously. The research employed a quantitative associative approach. The study took place at PT Bahtera Adi Jaya with a sample size of 60 employees, determined through a non-probability sampling technique known as saturation sampling. The data used were primary data collected through observation, questionnaires, literature review, and documentation. The results of the study revealed that: 1) Motivation had a positive and significant effect on the performance of PT Bahtera Adi Jaya employees, with a calculated t-value of 2.036 > the tabulated t-value of 2.002, and a significance value of 0.046 < 0.05. 2) Work discipline had a positive and significant effect on employee performance at PT Bahtera Adi Jaya, with a calculated t-value of 2.280 > the tabulated t-value of 2.002, and a significance value of 0.026 < 0.05. 3) Motivation and work discipline, when considered simultaneously, had a positive and significant impact on the performance of PT Bahtera Adi Jaya employees, with a calculated F-value of 6.837 > the tabulated F-value of 3.16, and a significance value of 0.002 < 0.05. The coefficient of determination was 19.3%, indicating that the remaining percentage was influenced by other variables not covered in the study.